Risk-Based Supervision of Pension Institutions in Denmark - van Dam, Rein; Andersen, Erik Brink (Washington, DC: World Bank, 2012)
This paper examines the move towards risk-based supervision of pension institutions in Denmark. Although Denmark has not adopted a comprehensive model to assess risk it has developed a number of building blocks which it uses for risk-based assessment. The motivations for improving risk assessment include a desire to identify emerging problems, and concerns about the solvency of pension institutions. In Denmark there is extensive use of guaranteed minimum returns in both the accumulation and payout phases which create substantial obligations on pension institutions, and focus attention on the integrity and solvency of the institutions which provide them. In conjunction with freeing up investment restrictions and moving towards market valuation of assets, the supervisor has introduced a 'traffic light' stress test model which calculates the effect of several market scenarios - the red test which is the more plausible and the yellow test which is possible but less likely. In addition to the use of the traffic light system, there has been a growing emphasis on the adequacy of internal risk control systems and greater reliance on market discipline. Pension institutions have sought to reduce their exposure to market volatility by better matching of assets and liabilities. There is a much better understanding of the risks inherent in the pension institutions' portfolios, and there has been a substantial increase in the use of hedging instruments.